Measurement of (1)H-(15)N and (1)H-(13)C residual dipolar couplings in nucleic acids from TROSY intensities - Ying, Jinfa (2011)
Analogous to the recently introduced ARTSY method for measurement of one-bond (1)H-(15)N residual dipolar couplings (RDCs) in large perdeuterated proteins, we introduce methods for measurement of base (13)C-(1)H and (15)N-(1)H RDCs in protonated nucleic acids. Measurements are based on quantitative analysis of intensities in (1)H-(15)N and (13)C-(1)H TROSY-HSQC spectra, and are illustrated for a 71-nucleotide adenine riboswitch. Results compare favorably with those of conventional frequency-based measurements in terms of completeness and convenience of use. The ARTSY method derives the size of the coupling from the ratio of intensities observed in two TROSY-HSQC spectra recorded with different dephasing delays, thereby minimizing potential resonance overlap problems. Precision of the RDC measurements is limited by the signal-to-noise ratio, S/N, achievable in the 2D TROSY-HSQC reference spectrum, and is approximately given by 30/(S/N) Hz for (15)N-(1)H and 65/(S/N) Hz for (13)C-(1)H. The signal-to-noise ratio of both (1)H-(15)N and (1)H-(13)C spectra greatly benefits when water magnetization during the experiments is not perturbed, such that rapid magnetization transfer from bulk water to the nucleic acid, mediated by rapid amino and hydroxyl hydrogen exchange coupled with (1)H-(1)H NOE transfer, allows for fast repetition of the experiment. RDCs in the mutated helix 1 of the riboswitch are compatible with nucleotide-specifically modeled, idealized A-form geometry and a static orientation relative to the helix 2/3 pair, which differs by ca 6° relative to the X-ray structure of the native riboswitch.